“Favela-senzala” a partir do olhar memorialístico de Conceição Evaristo, em Becos da Memória - Lima, Kayanny Elidja de (2024)
This research focuses on Conceição Evaristo's novel Becos da Memória, which depicts the process of de-slumification via the experiences of several characters. The narrator, Maria-Nova, introduces readers to Vó Rita, Maria-Velha, Negro Alírio, Bondade, and Tio Totó, who bring the story to life and offer light on the problems of living in the slums. This narrative technique reflects the author's literary objective, escrevivência. With this in mind, the goal of this study is to define the feature of memory in the novel, viewing it as a component of escrevivência, as exhibited through the narrator-character. To achieve this goal, the theoretical-methodological framework incorporates Halbwachs (1990) and Pollak's (1989) approaches to individual, collective, official, and subterranean memory; Martins' (2021) concepts of ancestry and orality; and Seligmann-Silva's (2008) concepts of trauma and testimony. Additionally, the discourses on griots in Cruz (2019) and Nascimento (2021), as well as Black literature in Cuti (2010) and Azevedo (2021), are added. Applying these notions to Conceição Evaristo's novel led to the following results: (i) It was confirmed that the subject is constructed by memory; (ii) the author's description of the slum space parallels that of slave quarters; (iii) the process of de-slumification is a new form of erasing for the Black population. Conceição Evaristo's literary project incorporates race and class issues, suggesting that the collective memory in Becos da Memória promotes resistance to erasure by official memory by preserving the Black community's memory.